EFEKTIVITAS MERONCE KARTU HURUF TERHADAP KEMAMPUAN MENGENAL HURUF ANAK USIA DINI DI PAUD A. SOPYAN KARAWANG - Asitoh, Aas; Arifudin, Opan; Chusnarin Haryanti, Heny (SIBATIK JOURNAL: Jurnal Ilmiah Bidang Sosial, Ekonomi, Budaya, Teknologi, Dan Pendidikan, 2025)
Letter recognition ability is one of the essential aspects of early literacy development in young children; however, many still experience difficulties in mastering this skill. This condition requires innovative learning that is both creative and interactive. This study aimed to examine the effectiveness of lettercard stringing activities in improving the letter recognition ability of children aged 5–6 years at PAUD A. Sopyan Karawang. The research employed classroom action research conducted in two cycles, each consisting of planning, action implementation, observation, and reflection stages. The subjects were group B children, and data were collected through observation, interviews, and documentation, then analyzed qualitatively and with simple quantitative calculations. The results indicated an improvement in children’s letter recognition ability from an average of 69.44% in the first cycle to 81.71% in the second cycle, accompanied by an increase in teacher activity from 68.05% to 84.72%. These findings show that lettercard stringing activities can enhance children’s cognitive skills in recognizing letters while also developing fine motor skills, concentration, and active participation in learning. The study concludes that letter-card stringing is effective as a creative learning strategy to improve letter recognition ability in early childhood education.